Quality assessment of clinical practice guidelines for Chagas disease (2015)
Introduction: The development of clinical practice guidelines (CPGs) has increased; this study aimed to assess the quality of CPGs for the management of Chagas disease. Methods: Following a systematic search of the scientifi c literature, two reviewers assessed the eligible guidelines using the Appraisal of Guidelines Research and Evaluation (AGREE) II instrument. Results: Five CPGs were included. The AGREE domains of scope/purpose, stakeholder involvement, and clarity of presentation were rated well, and the domains of applicability and editorial independence received poor ratings. Conclusions: The quality of CPGs for Chagas disease is poor, and signifi cant work is required to develop high-quality guidelines.